PERILAKU INVESTOR : âHERDING AND FEEDBACK TRADINGâ DI BURSA EFEK INDONESIA PERIODE 2012 - 2014 - Harsalim, Novita (University of Surabaya, 2015)
This study aims to examine investor behavior of herding and feedback trading in IDX at period 2012 â 2014. Where the indicator of herding and feedback trading adopted from Oh et al ( 2007 ) is net investment flows. This study research of two types investor, foreign and domestic.Â Â This study uses a quantitative approach to VAR model. This study uses a sample of investor in IDX period 2012 â 2014 and the sampel used in this study were 36 obserrvations. Using unit root test and lag optimal, the model can be more accurate.Â Â This study findings that foreign and domestic investor has been herding and feedback trading. Domestic investor behavior has influenced by return at 3rd period before, and foreign investor behavior has influenced by net investments domestic at 5th and 8th period before.